Telitacicept for lupus nephritis with BAFF and APRIL double positivity in children: a case report - Yang Meng; Meng Ying; Zhao Hongwen; Huang Li; Tang Xiaopeng (BMC Pediatrics)
Abstract We present a case of pediatric lupus nephritis (LN) with double positivity for BAFF and APRIL, highlighting the efficacy and safety of telitacicept in achieving complete remission. The patient, a 14-year-old Chinese male, presented with severe renal impairment and thrombotic microangiopathy (TMA). Conventional treatments were ineffective, and the patient experienced severe adverse reactions to rituximab. Subsequent treatment with telitacicept and sirolimus led to significant clinical improvement. After 6 months of follow-up, the patient achieved complete remission with an SLEDAI score of 0. This case underscores the potential of precision medicine in LN treatment. Individualized treatment based on pathological mechanisms is necessary, and telitacicept can improve the prognosis of lupus nephritis with good safety.